What differentiates university students who display high and low levels of entrepreneurial intensity? On individual characteristics, cognitions and the perception of business success - Pawel Ziemianski (Jesuit University Ignatianum in Krakow, 2019)
RESEARCH OBJECTIVE: The objective of the current paper is to verify in what way university students who declare high individual level of entrepreneurial intensity differ from those who are characterized by its intensity level. THE RESEARCH PROBLEM AND METHODS: A statistical analysis of obtained survey results was conducted. The group of research participants included 413 business students. Following statistical methods were used to analyze the data: internal reliability test, chi-square test of independence, independent samples t-test. THE PROCESS OF ARGUMENTATION: The line of reasoning presented in the current paper starts with the analysis of entrepreneurial intensity which, when measured on an individual level, is distinctive to people who declare a strong commitment to following an entrepreneurial career. Later the theoretical background including individual characteristics and cognitions that can potentially be prevalent among entrepreneurs is presented. RESEARCH RESULTS: It was found that groups of students who display high and low levels of entrepreneurial intensity differ significantly. These differences pertain to individual characteristics (i.e. gender), the perception of business success indicators and the perception of entrepreneurs' environment favorability. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: Obtained results allow to formulate conclusions about ways in which the development of entrepreneurial attitudes can be facilitated. Several recommendations are proposed for educators and policy makers including adopting a more fine-grained approach to supporting the emergence of entrepreneurial culture in Poland.